The impact of the total tax rate reduction on public services provided in Romania - TRANDAFIR, Adina (Annals of Spiru Haret University. Economic Series, 2014)
Against the background of economic globalization, governments tend to take tax measures disadvantageous to society in order to increase the attractiveness of the business environment. A common measures for this purpose is the reduction in tax rate. According to the classical theory of tax competition such measure leads to under the provision of public goods. This article aims to show, through an econometric analysis, whether in Romania, in the period 2006-2013, reducing total tax rate had a negative impact on public services. For this, using linear regression technique, the article analysed the correlation between total tax rate and the variation in the share of the main public service spending in GDP.